TRANSLATION STRATEGIES AND SEMANTIC TRANSFORMATION IN THE ENGLISH RENDERING OF ALEXANDER FAYNBERG’S POETRY - Abdumalikova Sevinch Tayirovna, (Ta'limda raqamli texnologiyalarni tadbiq etishning zamonaviy tendensiyalari va rivojlanish omillari, 2026)
Abstract: This article examines the translation strategies and semantic transformations involved in rendering the poetry of Alexander Faynberg from Russian into English. Translating Faynberg presents a dual challenge: preserving the rigorous formal structures of Russian versification while capturing the subtle "Eastern" semantic nuances inherent in his imagery. Using a comparative linguistic framework, the study analyzes the shifts in meaning (semantic loss and gain) that occur during the translation process. The research focuses on the "foreignization" versus "domestication" strategies employed by translators to handle culture-specific concepts (realia) and metaphorical clusters. The findings highlight how certain semantic layers of Faynberg’s identity—specifically those rooted in Central Asian philosophy—undergo transformation when adapted for an Anglophone audience. This study contributes to the field of Translation Studies by providing a model for analyzing the translatability of "hybrid" cultural texts.